Chapter I fattori soggettivi nel «moderno capitalismo». La complicata ricezione italiana e le questioni insolute nel pensiero di W. Sombart - Gioia, Vitantonio (Studi e saggi, 2020)
W. Sombart has always represented "a significant intellectual puzzle", but, beyond the contradictory (often overemphasised) aspects of his thought, he continues to be an interesting object of study, because of the innovative capacities that he showed in the analysis of the many original phenomena characterising the historical evolution of "modern capitalism". His innovative approach emerges in his interpretation, not always linear and univocal, of thinkers such as Marx and Schmoller, in his analysis of the relationship between religion and capitalism (and in his comparison with M. Weber on this specific aspect), and, finally, in his reconstruction of the distinctive features of the phases of development of capitalism analysed in his Der moderne Kapitalismus.